Сетевая система контроля технологического процесса выращивания полупроводниковых кристаллов и тонких пленок - Rogov, R. V.; Melnychuk, S. V.; Vorobets, G. I. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A model of a technological network has been proposed and software developed for monitoring parameters and controlling the modes of the technological process of semiconductor crystal and thin-film growth. DLL libraries have been created to provide communication between the client and server parts of the network. The system implements process parameter monitoring, measurement data archiving, and event logging at the objects of the system. The universality of the software makes it possible to optimize the design and setup of a technological network for arbitrary types of equipment.